Bitter taste receptor T2R14-Gαi coupling mediates innate immune responses to microbial quorum sensing molecules in cystic fibrosis - Nisha Singh; Ryan H. Cunnington; Anjali Bhagirath; Ankita Vaishampayan; Mohd Wasif Khan; Tejas Gupte; Kangmin Duan; Abdelilah S. Gounni; Shyamala Dakshisnamurti; John W. Hanrahan; Prashen Chelikani (iScience)
Summary: Cystic fibrosis (CF) is an autosomal recessive disease characterized by microbial infection and progressive decline in lung function, leading to significant morbidity and mortality. The bitter taste receptor T2R14 is a chemosensory receptor that is significantly expressed in airways. Using a combination of cell-based assays and T2R14 knockdown in bronchial epithelial cells from CF and non-CF individuals, we observed that T2R14 plays a crucial role in the detection of bacterial and fungal signals and enhances host innate immune responses. Expression of Gαi protein is enhanced in CF bronchial epithelial cells and T2R14-Gαi specific signaling leads to increased calcium mobilization. Knockdown of T2R14 leads to reduced innate immune activation by bacterial strains deficient in quorum sensing. The results demonstrate that T2R14 helps protect against microbial infection and thus may play an important role in the innate immune defense of the CF airway epithelium.